A Comparative Study of Muscle Symptoms of Atorvastatin with Rosuvastatin in Patients of Atherosclerotic Cardiovascular Disease - Rashed, Md Rakibul Hasan; Banerjee, Sajal Krishna; Ahsan, Syed Ali; Zaman, SM Mustafa; Ahmed, Khurshed; Rahman, Md Mukhlesur; Mahmood, Manzoor; Arzu, Jahanara; Adhikary, Dipal Krishna; Rabbani, Md Golam Hossain; et al. (University Heart Journal, 2018)
Background: Statins are the corner stone therapy of atherosclerotic cardiovascular disease (ASCVD). Statins may cause myalgia, myotoxicity, myopathy and rhabdomyolysis along with its lipid lowering properties and pleiotropic effects. Statins associated muscle symptoms (SAMS) are the leading cause of nonadherent and discontinuation. This study was conducted to evaluate and understand the muscle symptoms of high intensity statin therapy (atorvastatin 40 mg and rosuvastatin 20 mg) for a period of three months in individual patient with clinical atherosclerotic cardiovascular disease. Methods: A total of 280 patients with clinical atherosclerotic cardiovascular disease were studied to once daily atorvastatin 40 mg and rosuvastatin 20 mg. It was a randomized controlled single blind trial. The primary end point was muscle symptoms-muscle pain, fatigue, cramp/spasticity and weakness at 4 weeks and in 3 months of study period. Serum creatinine kinase was measured in every patient with muscular symptoms. Results: Patients of atorvastatin group noticed severe pain more than rosuvastatin group at the end of 3 months of treatment period (14.21% vs 4.38%, p <0.05), respectively). Significantly more patients felt extremely bad (12.78% vs 4.38%, p <0.05) and bad (24.66% vs 14.52%, p <0.05) with atorvastatin compared with rosuvastatin. Patients of atorvastatin group showed more marked increase muscle spasm (3.76% vs 1.46%, p <0.05) and slight increase muscle spasm (36.27% vs 16.01%, p <0.05) than rosuvastatin group by spasticity grade. One patient of atorvastatin group developed considerable increase in muscle spasm. Medical research council (MRC) muscle power grade 4 between atorvastatin and rosuvastatin group was observed 20.05% vs 10.90%, p <0.05, respectively. Three patients of atorvastatin group developed grade 3 muscle power. Serum creatine kinase > 1500 U/L was observed more in atorvastatin than rosuvastatin group (14.21% vs 4.38%, p <0.05, respectively). Statin associated muscle symptoms (more severe muscle problem, myositis/myopathy) observed more in atorvastatin than that of rosuvastatin group ( 34.07% vs 13.08% , p <0.05, respectively). Both treatments were well tolerated. No cases of rhabdomyolysis, incident diabetes, hepatic or renal insufficiency were recorded during the study period. Conclusion: Rosuvastatin had better outcome profile of muscle symptoms than atorvastatin in patients with clinical atherosclerotic cardiovascular disease among the Bangladeshi population. Patients in atorvastatin group experienced more muscle pain, fatigue, cramp/spasticity and weakness than rosuvastatin. University Heart Journal Vol. 14, No. 1, Jan 2018; 9-20